The Christian politician? An investigation into the theological grounding for Christians" participation in politics - Tshaka, Rothney (HTS teologiese studies, 2016)
Party politics is a controversial subject in mainline ecclesiastical circles in South Africa. While one can be forgiven for thinking that this perception changed after 1994, the reverse seems to be the case. This article is an attempt to start a conversation on the subject of Christian leaders’ participation in politics. It will become clear from this article that the entrenched idea of the separation between the material and the spiritual is problematic. Acknowledging the sensitivity around this subject, this article aims to intentionally engage the involvement of Christian leaders in party politics. This is done in a positive albeit careful manner simply because the need for ethical leadership in present-day South Africa has become urgent.